Evaluating the effectiveness of wildlife educational program on knowledge, attitude and awareness among three selected secondary schools students in Perak, Malaysia - Arumugam, Kalai Arasi; Ismail, Nor Hidayatul Solehah; Shohaimi, Shamarina; Annavi, Geetha (Chronopub Publications, 2019)
Habitat loss and wildlife encroachments have been the major factors diminishing the wildlife populations globally. Wildlife conservationists around the world are working hard to sustain wildlife populations through various possible ways, and one of them is through cultivating the awareness among young generation especially school children. In this study, we analysed the level of knowledge, awareness and attitude about wildlife among three selected secondary school students in Perak, Malaysia through a self-administered survey. The analysis was separated into two parts; pretest and post-test, which was before and after mini education program called 'Care for Wild Animal' was conducted. Results from this study showed lower secondary school students (aged 13 years old) have lower level of knowledge and awareness on wildlife compared to upper secondary students (aged 16 years old). Male students had more knowledge and awareness towards wildlife and the conservations compared to female student who were culturally limited to external exposure. We believe that limited details of wildlife education in school syllabus could be the reason for the difference. Therefore, incorporating more information or a specific chapter on wildlife education and conservation starts from elementary school level will benefit the environment and the future of wildlife in our Malayan ecosystem and to produce nature loving generations.